Áp dụng BĐT sau:
[tex]a^3+b^3+c^3-3abc=(a+b+c)(a^2+b^2+c^2-ab-bc-ca)[/tex]
Ta thay c=1 có:
[tex]a^3+b^3+1^3-3ab=(a+b+1)(a^2+b^2+1-ab-b-a)\\\rightarrow a^3+b^3+1-3ab=(a+b+1)(a^2+b^2+1-ab-b-a)[/tex] (1)
từ đề bài có:
[tex]a^3+b^3=3ab-1\rightarrow a^3+b^3+1-3ab=0[/tex] (2)
Từ (1) và (2) suy ra
[tex](a+b+1)(a^2+b^2+1-ab-b-a)=0[/tex]
mà a+b+1 >0 ( vì a;b dương)
Suy ra [tex](a^2+b^2+1-ab-b-a)=0\\\rightarrow 2a^2+2b^2+2-2ab-2b-2a=0\\\rightarrow (a-b)^2+(a-1)^2+(b-1)^2=0\\\rightarrow a=b=1[/tex]
Suy ra [tex]a^{2018}+b^{2018}=1^{2018}+1^{2018}=2(dpcm)[/tex]